Comparison of Visual Outcomes After Femtosecond LASIK, Wave Front-Guided Femtosecond LASIK, and Femtosecond Lenticule Extraction. Issue 8 (August 2016) - Zheng, Yan; Zhou, Yue-Hua; Zhang, Jing; Liu, Qian; Zhang, Li; Deng, Zheng-Zheng; Li, Shi-Ming
Abstract : Purpose: To compare the mesopic contrast sensitivity (CS) and higher order aberrations (HOAs) at 3 months after femtosecond–laser in situ keratomileusis (LASIK) (FS-LASIK), wave front–guided femtosecond LASIK (WF-LASIK), and femtosecond lenticule extraction (FLEx) for the correction of myopia and myopic astigmatism. Methods: In this prospective nonrandomized study, 332 right eyes of 332 patients were treated with FS-LASIK, WF-LASIK, or FLEx. The HOAs and mesopic CS were evaluated preoperatively and at 3 months postoperatively. Results: At 3 months of follow-up, 98 eyes (96.1%) of the FS-LASIK group, 92 eyes (98.9%) of the WF-LASIK group, and 133 eyes (96.4%) of the FLEx group had an uncorrected distance visual acuity of 20/20 or better. The HOAs improved from 0.34 μm during preoperative examination to 0.56 μm of the end of the follow-up in the FS-LASIK group, from 0.31 to 0.41 μm in the WF-LASIK group, and from 0.32 to 0.54 μm in the FLEx group (all P < 0.01). At a spatial frequency of 12 cycles per degree, a better mesopic CS was observed in the WF-LASIK group (1.47) than in the FS-LASIK (1.36) and FLEx (1.33) groups ( P < 0.01); a better mesopic CS with glare was also noted in the WF-LASIK group (1.37) than in the FS-LASIK (1.25) and FLEx (1.29) groups ( P < 0.01). Conclusions: The FS-LASIK, WF-LASIK, and FLEx procedures result in comparable refractive results at 3 months postoperatively. However, there is improvement in the mesopic CS and HOAs after WF-LASIK.